Kebutuhan Akan SDM Doktrin Ekonomi (Konsep MSDM, Identifikasi Nilai SDM, Penawaran dan Permintaan Tenaga Kerja dan Karakteristik Tenaga Kerja Terdidik, Upaya Pengembangan SDM) - Khairul Azan; Lias Hasibuan; Kasful Anwar Us (STAIN Bengkalis, 2021)
Human resources have a close relationship with growth. The economy will improve when it has quality resources. Given the close relationship, the need for human resources must be adjusted to economic demands. The existence of the demands implies a workforce that is relevant to the world of work and meets the standards that have been set. This article aims to describe the concept of the need for human resources and economic doctrine from the point of view of the concept of HR, identification of the value of human resources, supply and demand for labor and labor characteristics, HR development efforts. The method used is qualitative with the type of library research. The conclusion of this article shows that in order for quality human resources, there must be developed according to the times, especially now that we are entering a new era known as the industrial revolution 4.0 where technology begins to dominate. The process of developing human resources can be done through education. Therefore, so that educational products can answer the challenges of changes that occur, it is necessary to redesign the educational system.